A Comparison of Linear and Undulating Periodization for Improving Muscular Strength and Strength Endurance in Men - Niknafs, Saba (2008)
The purpose of the study was to determine if significant differences exist between two different periodization programs (linear and undulating), in eliciting superior gains in maximum strength and strength endurance for the back squat and bench press. Twenty (n=20) sports science university students underwent a 15-wk resistance-training program. They were tested for the one-repetition maximum (lRM) back squat, IRM bench press, upper-body strength endurance (80% IRM bench press), lower-body strength endurance (80% IRM back squat), body-fat percentage, power (Wingate test), thigh and arm circumferences, and changes in body mass. Following initial testing, participants were randomly assigned to either linear periodization (LP) or undulating periodization (UP) training. Participants performed both the bench press and the back squat three days a week throughout the training period with volume and intensity equated for both groups at the end of training. The LP group linearly changed intensity and volume over each 4-wk training phase, while the UP group changed intensity and volume daily. Participants were then re-tested at the end of each 4--wk training phase and training loads were then adjusted according to the new 1 RM. Repeated measures ANOVA were conducted to examine differences between groups. Maximum strength and strength endurance for both bench press and back squat increased significantly from pre to post test for both groups (bench press maximum strength increased from 50.5 kg to 62.8 kg and 50.3 kg to 61.5 kg for LP and UP groups respectively and bench press strength endurance increased from 5.5 repetitions to 10.6 repetitions and 6.2 repetitions to 11.2 repetitions for LP and UP groups respectively). However, there was no significant difference in pre-post strength and strength endurance measures in the LP group compared to the UP group. Each of the two models proved effective in increasing bench press and back squat strength and strength endurance over the course of fifteen weeks.